Enhancing Pre-service Mathematics Teachers' Mathematical Literacy Through Project-Based Learning - Sudianto, Sudianto; Laelasari, Laelasari; Julia, Rida (Al-Mufid, 2023)
This quasi-experimental study investigates the effect of Project-Based Learning (PjBL) integration within an online platform on the mathematical literacy of 32 pre-service mathematics teachers at Majalengka University, Indonesia. Utilizing purposive sampling and categorizing participants based on their mathematical ability, the study assessed the impact of PjBL on enhancing mathematical literacy in real-world contexts. The one-group pretest-posttest design was adopted, and statistical analyses were performed using paired sample t-tests and one-way ANOVA. The results demonstrated a significant increase in post-test mathematical literacy scores, with initial mathematical ability positively correlating with these scores. A post hoc Least Significant Difference (LSD) test further highlighted significant differences across various initial mathematical ability levels. The study concludes that PjBL is an effective strategy for improving mathematical literacy, reflecting a meaningful distinction in pre-service primary school teachers' pretest and post-test scores. The research offers valuable insights into enhancing mathematical literacy in Indonesia, emphasizing the relevance of PjBL, particularly in the context of the pandemic, and preparing future educators to meet global challenges.